2019
DOI: 10.1039/c9qo00440h
|View full text |Cite
|
Sign up to set email alerts
|

A one-pot protocol for the synthesis of β-ketosulfones from α,α-dibromoketones

Abstract: A one-pot debromination/sulfonylation strategy was developed for the direct transformation of α,α-dibromoketones into β-ketosulfones in the presence of sulfinate salts in a methanol solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…As important and useful synthetic building blocks and fragments, β-ketosulfones and allylsulfones have been broadly applied in the fields of pharmaceuticals and organic synthesis. [52][53][54] Lu and co-workers developed the first Cu-catalyzed or visible-light-catalyzed cyanoalkylsulfonylation of vinyl triflates or allyl trifluoromethylsulfones with cyclobutanone oximes via the in situ capture of SO 2 by cyanoalkyl radicals, obtained from cyclobutanone oximes (Scheme 12). 55 It was found that various functional groups such as halogen, nitro, cyano, ester or methoxy groups were all suitable for the optimal catalytic system.…”
Section: Ke-wenmentioning
confidence: 99%
“…As important and useful synthetic building blocks and fragments, β-ketosulfones and allylsulfones have been broadly applied in the fields of pharmaceuticals and organic synthesis. [52][53][54] Lu and co-workers developed the first Cu-catalyzed or visible-light-catalyzed cyanoalkylsulfonylation of vinyl triflates or allyl trifluoromethylsulfones with cyclobutanone oximes via the in situ capture of SO 2 by cyanoalkyl radicals, obtained from cyclobutanone oximes (Scheme 12). 55 It was found that various functional groups such as halogen, nitro, cyano, ester or methoxy groups were all suitable for the optimal catalytic system.…”
Section: Ke-wenmentioning
confidence: 99%
“…A variety of aromatic and aliphatic α,α-dibromo ketones were found to be suitable substrates to react with sodium p -tolylsulfinate to furnish widespread β-keto sulfones in good to high yields ( Scheme 142 ). 207 Acyclic dibromo ketones and cyclic substrates also led to the tosylated products. Besides sodium p -tolylsulfinate, other aryl sulfinates bearing fluoro- and chloro-substituents, as well as sodium methanesulfinate were successfully employed to produce the desired products in good yields.…”
Section: Applications Of Sodium Sulfinatesmentioning
confidence: 99%
“…Recently Xia et al., reported a one‐pot di‐dehalogenation‐sulfonylation protocol starting from α,α‐dihaloketones 88 (Scheme ). A large number of β‐ketosulfones 89 a – 89 e were synthesized via mono‐dehalogenation followed by nucleophilic substitution at α‐halocarbon of 88 a .…”
Section: αα‐Dihaloketones As Building Blocks In Organic Synthesismentioning
confidence: 99%